THE RISK PREFERENCES OF ENTREPRENEURS IN INDONESIA. (9th June 2016) - Sohn, Kitae
ABSTRACT: Entrepreneurship is known to be important for innovation and economic growth, but relatively little attention has been paid to entrepreneurs in developing countries. We examined an important aspect of entrepreneurship: risk‐taking. We analysed the Indonesian Family Life Survey and compared risk preferences between entrepreneurs and non‐entrepreneurs. We found that risk tolerant workers were more likely to be entrepreneurs than risk averse workers by about 5 percentage points, or about 20 percent of the proportion of entrepreneurs in the labour force. The results imply that not all entrepreneurs in Indonesia are pushed into the sector; some actively take risks and seek innovations.